Frequency of Hemorrhage on Follow Up Imaging in Stroke Patients Treated With rt-PA Depending on Clinical Course - Schurig, Johannes; Haeusler, Karl Georg; Grittner, Ulrike; Nolte, Christian H.; Fiebach, Jochen B.; Audebert, Heinrich J.; Endres, Matthias; Rocco, Andrea (Frontiers in Neurology, 2019)
Background According to current guidelines, stroke patients treated with rt-PA should undergo brain imaging to exclude intracerebral bleeding 24 hours after thrombolysis, before the start of medical secondary prevention. However, the usefulness of routine follow-up imaging with regard to changes in therapeutic management in patients without neurological deterioration is unclear. We hypothesized that follow up brain imaging solely to exclude bleeding in patients who clinically improved after rt-PA application may not be necessary. Methods Retrospective single-center analysis including stroke patients treated with rt-PA. Records were reviewed for hemorrhagic transformation one day after systemic thrombolysis and brain imaging-based changes in therapeutic management. Twenty-four hours after thrombolysis patients were divided into four groups: 1) increased NIHSS score; 2) unchanged NIHSS score; 3) improved NIHSS score and; 4) NIHSS score =0. Results Out of 188 patients (mean age 73 years, 100 female) receiving rt-PA, 32 (17%) had imaging-proven hemorrhagic transformation including 11 (6%) patients with parenchymal hemorrhage. Patients in group 1) and 2) more often had hypertension (p=0.015) and more often had parenchymal hemorrhage (9% vs. 4%; p<0.206) compared to group 3) and 4) and imaging-based changes in therapeutic management were more frequent (19% vs. 6%; p=0.007). Patients of group 3) and 4) had no changes in therapeutic management in 94% of the cases. Patients in group 4) had no hemorrhagic transformation in routine follow-up brain imaging. Conclusions Frequency of hemorrhagic transformation in Routine follow-up brain imaging and consecutive changes in therapeutic management were different depending on clinical course measured by NHISS score.